KEPEMIMPINAN PEREMPUAN DALAM ISLAM - Muhajir (Al-Qadha, 2018)
This paper is a simple and concise study conducted in Langsa City, especially in severalsub-districts. To parse this paper well, the author gives the title: "Women's Leadership in Islam(Study of Perspective Analysis Ulama dayah of Langsa City for Mayor Candidates)". Then, in thispaper we will discuss gender understanding at the beginning of the discussion, gender equality basedon international law, women in Islam and analysis of women as candidates for mayors in LangsaCity according to the perspective of dayah scholars.